2022
DOI: 10.1371/journal.pone.0274158
|View full text |Cite
|
Sign up to set email alerts
|

Using ISARIC 4C mortality score to predict dynamic changes in mortality risk in COVID-19 patients during hospital admission

Abstract: As SARS-CoV-2 infections continue to cause hospital admissions around the world, there is a continued need to accurately assess those at highest risk of death to guide resource use and clinical management. The ISARIC 4C mortality score provides mortality risk prediction at admission to hospital based on demographic and physiological parameters. Here we evaluate dynamic use of the 4C score at different points following admission. Score components were extracted for 6,373 patients admitted to Barts Health NHS Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
3
1
Order By: Relevance
“…Several studies evaluate the dynamic use of the ISARIC 4C score at admission, using AUC to assess score discrimination on admission. In COVID-19 patients, Crocker-Buque et al [45] obtained an AUC of 0.71 (95% CI: 0.69-0.74), while Jones et al in a validation study, obtained an AUC of 0.77 (95 CI 0.79-0.87) at admission [45,46]. These AUCs appear to perform less well than the one obtained with our CZ-COVID-19 Score on admission.…”
Section: Discussioncontrasting
confidence: 52%
“…Several studies evaluate the dynamic use of the ISARIC 4C score at admission, using AUC to assess score discrimination on admission. In COVID-19 patients, Crocker-Buque et al [45] obtained an AUC of 0.71 (95% CI: 0.69-0.74), while Jones et al in a validation study, obtained an AUC of 0.77 (95 CI 0.79-0.87) at admission [45,46]. These AUCs appear to perform less well than the one obtained with our CZ-COVID-19 Score on admission.…”
Section: Discussioncontrasting
confidence: 52%
“…This scoring system is derived from a comprehensive population cohort study conducted at the national level in the United Kingdom. 21 Understanding the clinical course of COVID-19 is crucial until a viable vaccination becomes widely accessible, due to the lack of specific therapies and the tremendous health and economic impact of the pandemic. 1,22 In this situation, deficient vitamin D is a modifiable risk factor due to its safety and affordability.…”
Section: Resultsmentioning
confidence: 99%
“…Another study from Saudi Arabia found that the ISARIC 4C Mortality Score is an excellent tool to predict mortality in critically ill COVID-19 patients with an AUC of 0.81; the sensitivity was 70.5% and the specificity 73.97% with a cutoff value of >9 [ 22 ]. In addition, Crocker-Buque et al support using the ISARIC 4C Mortality Score for triaging COVID-19 patients at the time of admission and as a dynamic tool that provides accurate mortality risk information at any time during the hospitalization of COVID-19 patients [ 34 ].…”
Section: Discussionmentioning
confidence: 99%